Reverse logistics : emerging trends, opportunities and challenges - Liow, Jia Yin (2017)
In the recent years, reverse logistics have significantly gained attention from researchers and practitioners. Reverse logistics key activities comprise collection from the end user, classification, product recovery and waste disposal. In general, economic, legal and social issues are the main driver of reverse logistics practice. This paper put emphasis on the implementation of reverse logistics in the e-commerce market which the e-commerce market is formed due to the development and advancement in technology and globalization. The objective of the current study is to identify the solution of handling product return in the e-commerce context due to exclusive characteristics as compared to the traditional commerce market. Both of the e-commerce market and common strategies used to handle product return the traditional commerce market are identified as followed: return policy, pricing decision, forecasting, integration of forward-reverse logistics network and outsourcing. The main findings of this paper are three exclusive characteristics of e-commerce market that shaped the challenges in reverse logistics practice are as followed, no virtual shop, home delivery service and lower cost incurred from both customers and e-retailers. With the application of common strategies, the obstacles are overcome. Another distinguished characteristic of e-commerce is the massive utilization of website also discussed in the findings.